DAMPAK SMARTPHONE TERHADAP INTERAKSI SOSIAL MAHASISWA ASAL PEDESAAN - Trijuliani Renda; Aprilia Kaut (UNIVERSITAS SEBELAS MARET (UNS), 2024)
The use of smartphones in Indonesia is increasing, including in Kupang City, which affects the pattern of human social interaction with other humans in real and virtual encounters. This study aims to analyze the impact of smartphones on the interaction patterns of students from rural areas in Kupang City. The paradigm used in this study is constructivistic to focus on subjective understanding and individual experience with a qualitative approach. The method is a case study by taking data from 9 appropriate informants to obtain data through interviews in March-May 2023. The results showed: first, there was a change in students' misconceptions in using smartphones. Second, social interactions use smartphones as imitation and imitation, third but due to the disappearance of real space and virtual face boundaries, dissociative interactions shift to associative interactions that make students aware of using smartphones wisely. The implication of this research is the need to increase digital literacy among the younger generation.